Evaluation of domain wall motion in Mn-doped PMS-PZT ceramics under various hydrostatic pressures by nonlinear response measurements. Issue 9 (15th June 2018) - Chen, Caiyun; Liang, Ruihong; Zhou, Zhiyong; Nie, Xin; Zhang, Wenbin; Cao, Fei; Dong, Xianlin
Abstract: The nonlinear dielectric responses of both unpoled and poled Mn-doped PMS-PZT ceramics as a function of hydrostatic pressure were investigated. Based on the application of Rayleigh law analysis, the contribution of irreversible domain wall motion to the dielectric response under hydrostatic pressure was quantitatively evaluated. Initial increased irreversible extrinsic contribution to the dielectric responses were observed in both unpoled and poled samples which can be ascribed to the pressure induced domain wall pinning relaxation effect. In addition, the pressure induced depolarization effect may also facilitate domain related extrinsic contribution to dielectric response in poled samples. The present study may shed further light on understanding the domain wall motion dynamic in piezoelectric ceramics under the application of hydrostatic pressure and is quite helpful for the design and optimization of piezoelectric devices used in underwater areas.